Law Enforcement Model of Village Fund Corruption Through Adat Criminal Law Approach and Local Wisdom in West Sumatera - Aria Zurnetti; Nani Mulyati (Nagari Law Review, 2022)
Corruption in Indonesia has its own characteristics. Corruption crimes committed at the village level have caused losses to state finances. Countermeasures against corruption in village funds are required to be effective and firm, in order to be able to resolve and to reduce the number of corruption in the future. This paper discusses the pattern of corruption in West Sumatra, especially in the cities of Solok and Pariaman, and discusses the prevention model used against corruption. The methodology used to answer these problems is normative juridical research. The results of the study found that the pattern of corruption tended to vary in each region, such as double budget, mark-up, unilateral withdrawal of nagari funds by nagari administrators. However, there is a pattern that is always found in every case, namely not making a deposit of tax collection results, the tax money is intentionally not deposited and used for personal interests which causes state financial losses. Furthermore, countermeasures are taken repressively using Indonesian criminal law, as well as preventively by establishing a nagari regulation that uses a customary criminal law approach. West Sumatra has its local wisdom that is still alive and well maintained, even the community respects customary criminal law more than positive law, therefore preventive efforts by using the customary criminal law approach are expected to be able to create nagari that are free from corruption. In an effort to prevent corruption of village funds and Village Fund Allocation (ADD) by village officials, the government of Nagari Situjuah Batua, Situjuah Limo Nagari District, Lima Puluh Kota Regency, West Sumatra, made legal rules based on customary law. The regulation is stated in the Situjuah Batua Nagari Regulation Number 8 of 2019 concerning Prevention of Corruption, Collusion and Nepotism Based on the Salingka Nagari Customary Law